2009
DOI: 10.1002/lary.20152
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the muscular process for arytenoid adduction surgery

Abstract: The TTI window can be used intraoperatively to help locate the arytenoid muscular process during arytenoid adduction surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In AA surgery, identifying the location of the MP is important for both safety and success, and several reports have described less invasive methods for identifying the MP. 2, 11, 12 In EAAS, the most difficult tasks are aiming the penetration needle at the MP during its insertion through the cricothyroid space and intraluminal penetration of the piriform sinus. These tasks could result in failure or complications such as hematoma, mucosal laceration, and penetration of the endotracheal tube, especially when the procedure is performed by inexperienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…In AA surgery, identifying the location of the MP is important for both safety and success, and several reports have described less invasive methods for identifying the MP. 2, 11, 12 In EAAS, the most difficult tasks are aiming the penetration needle at the MP during its insertion through the cricothyroid space and intraluminal penetration of the piriform sinus. These tasks could result in failure or complications such as hematoma, mucosal laceration, and penetration of the endotracheal tube, especially when the procedure is performed by inexperienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…A cadaveric study by Mitchell et al found that the muscular process was located along a line extending posteriorly from the inferior border of a standard laryngoplasty window. 86 In males, the average distance was 27mm, whereas in females the distance was 19mm. The muscular process was consistently found an average of 2.7mm inferior to the midpoint between the roots of the superior and inferior cornu.…”
Section: Surgical Approachmentioning
confidence: 99%
“…101,102 Although commonly cited as a complication of arytenoid adduction, it is rarely reported in the literature. 66,86,88,94 …”
Section: Complicationsmentioning
confidence: 99%
“…When AA was first performed, a method for identifying the arytenoid cartilage was proposed based on anatomical studies. 12,13 To identify the arytenoid cartilage based on anatomical landmarks, it is necessary to remove the external laryngeal muscle and expose the thyroid cartilage plate. However, the external laryngeal muscles, pharyngeal constrictor muscles, external branch of the superior laryngeal nerve, and cricothyroid muscle function are auxiliary and compensatory for paralyzed vocal folds, whose function is reduced because of damage to the recurrent laryngeal nerve.…”
Section: Arytenoid Cartilage Positionmentioning
confidence: 99%